The Concept of Civilized Indonesian Law: Strengthening Islamic Spiritual Values in Law - Yogi Prasetyo; Leoncio Serazinho Amaral (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
This article aims to explain the concept of civility, legal problems in Indonesia that reflect uncivilization, and the idea of civilized law based on Islamic spiritual values. A secular understanding that separates law from good religious and spiritual values is an exciting background for research. This research uses a literature study method with a legal philosophy approach. Research data comes from literature and scientific works related to the research theme. The research results show that civility is related to good moral ethics by religious values. Research shows that legal problems originate from legal actors' wrong actions or moral ethics. Apart from that, the research results also explain the concept of civilized law with the principles of Islamic spiritual values, which are relevant to forming legal, moral ethics. So, it can be concluded that the concept of civilized law for Indonesia is to the current legal situation, which requires changes in the behavioral attitudes of legal actors by strengthening Islamic spiritual values. This research contributes as a behavioral guideline for policymakers and law implementers to present a more moral and ethical law based on morals and ethics (adab) based on spiritual values. This includes the formulation of professional ethics based on spiritual values. To present civilized legal behavior in Indonesia.